Undergraduate students perception on K-economy and globalisation: a case study in a Malaysian public university - Mustapha, Ramlee; Zainal Abiddin, Norhasni (The Journal of International Social Research, 2008)
A critical challenge that faces post-modern society is to attain full employment and sustain economic growth in the global economy. The future of Malaysia’s competitiveness depends on the knowledge and skills of its workforce. With the advent of K-economy and globalisation, the need for a strong human capital has never been so critical. Literature has shown that several Asia Pacific countries, including Malaysia, have spent relatively low percentage of their GDP on ICT infrastructure and R&D. As a result, there is a low percentage of skilled and knowledge workers (K-workers) in the population such as the scientists, engineers and ICT specialists. In addition, the level of innovative R&D is also low among these countries which resulted in few numbers of technopreneurs and entrepreneurs. Further, the percentage of graduates who are unable to secure proper jobs posed a challenge to the nation. Thus, the education and training system has to gear itself to meet the demands of the new economy. The purpose of this study was to examine critically the educational experience of students in a higher learning institution in terms of their educational readiness to meet and adapt to the paradigm shift brought about by globalisation and the K-economy.